High Energy Cosmic Rays - Stanev, Todor (Astronomy and Planetary Sciences, 2010)
Cosmic rays are an essential part of the universe. Their origin is related to many important astrophysical processes, such as star formation, stellar evolution, supernova explosions and the state of interstellar matter in the Galaxy. Cosmic Ray Physics reviews our present knowledge of cosmic rays, describing how they are born in a wide range of cosmic processes, how they are accelerated and how they interact with matter, magnetic fields and radiation during their journey across the Galaxy. The book also describes the detection of cosmic rays, and the processes which take place, both at the top and within the Earth's atmosphere. The author also describes the very important area of the underground detection of very high energy cosmic rays and particles such as neutrinos. The book is divided into two parts, the first describing the standard model of cosmic rays and contemporary challenges, and the second part dealing with very high energy cosmic rays that cannot be detected directly in satellite and balloon experiments, and with gamma-ray and neutrino astronomy. It is in this particular aspect of the book that the greatest developments have taken place during the 5 years since the first edition was completed. Consequently, it is in the chapters cosmic ray showers, their spectrum, on high energy neutrinos, and on gamma-ray astronomy of this revised and updated 2nd edition that a considerable amount of new material has been incorporated with more minor revisions and updating taking place in the first part of the book. Students and lecturers of advanced undergraduate courses on cosmic rays and astroparticle physics as well as post graduates and researchers will continue to find this book a valuable source of learning and reference.